Cropping pattern optimization considering uncertainty of water availability and water saving potential - Hao, Lina; Su, Xiaoling; Singh, Vijay P (International Journal of Agricultural and Biological Engineering, 2018)
In arid and semi-arid areas, the profitability of irrigated agriculture mainly depends on the availability of water resources and optimal cropping patterns of irrigation districts. In this study, an integrated agricultural cropping pattern optimization model was developed with considering the uncertainty of water availability and water saving potential in the future, aiming to maximize agricultural net benefit per unit of irrigation water. The available water which was based on the uncertainty of runoff was divided into five scenarios. The irrigation water-saving potential in the future was quantified by assuming an increase in the rate irrigation water-saving of 10% and 20%. The model was applied to the middle reaches of Heihe River basin, in Gansu Province, China. Results showed that if the irrigation water-saving rate was assumed to increase by 10%, then the net water-saving quantity would increase by 21.5-22.5 million m3 and the gross water-saving quantity would increase by 275.7-303.0 million m3. Similarly, if the irrigation water-saving rate increased by 20%, then the net water-saving quantity would increase by 43.0-45.1 million m3 and the gross water-saving quantity would increase by 331.7-383.2 million m3. If the agricultural cropping pattern was optimized, the optimal water and cultivated area allocation for maize would be greater than those for other crops. Under the premise that similar volume of irrigation water quantity was available in different scenarios, results showed differences in system benefit and net benefit per unit of irrigation water, for the distribution of available irrigation water was diverse in different irrigation districts.Keywords: cropping pattern optimization, irrigation water-saving potential, different scenarios, water availability, water use efficiency, particle swarm optimization (PSO)DOI: 10.25165/j.ijabe.20181101.3658Citation: Hao L N, Su X L, Singh V P. Cropping pattern optimization considering uncertainty of water availability and water saving potential. Int J Agric & Biol Eng, 2018; 11(1): 178–186.